New approach for spacing of movement joints in reinforced and unreinforced masonry veneer walls / Neue Bemessungsmethode für die Abstände von Dehnungsfugen in bewehrten und unbewehrten Verblendmauerwerksschalen: Part 2: Reinforced masonry / Teil 2: Bewehrtes Mauerwerk. Issue 6 (December 2016) - Martens, Dirk R.W.
Abstract: The first part of the paper, published in issue 4 [3] and dealing with the spacing of movement joints, described the design method for unreinforced masonry veneer walls. This paper focuses on increasing the spacing of movement joints by applying bed joint reinforcement. The proposed approach enables manufacturers of bed joint reinforcement to provide recommendations for the spacing of movement joints for bed joint reinforced veneer walls dependent upon the allowable crack width, the reinforcement type, the diameter and the vertical spacing of the reinforcement.